2008
DOI: 10.1038/onc.2008.390
|View full text |Cite
|
Sign up to set email alerts
|

The α-receptor for platelet-derived growth factor as a target for antibody-mediated inhibition of skeletal metastases from prostate cancer cells

Abstract: Bone resorption by osteoclasts is thought to promote the proliferation of prostate cancer cells disseminated to the skeleton (Mundy, 2002). Using a mouse model of experimental metastasis, we found that although latestage metastatic tumors were indeed surrounded by osteoclasts, these cells were spatially unrelated to the small foci of cancer cells in early-stage metastases. This is the first evidence that survival and growth of disseminated prostate cancer cells immediately after their extravasation may not dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
52
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 31 publications
5
52
0
Order By: Relevance
“…The correct penetration of the cardiac wall was established by the appearance of fresh arterial blood in the LuerLok fitting of the hypodermic needle. In addition, blue-fluorescent polystyrene beads (10 μm diameter; Invitrogen, Molecular Probes) were coinjected with cancer cells and their detection in the adrenal glands was utilized to confirm successful inoculation in the blood circulation (51,52). Animals were sacrificed after 72 hours, and adrenal glands and bones were fixed in 4% formalin for 48 hours.…”
Section: Figure 10mentioning
confidence: 99%
See 1 more Smart Citation
“…The correct penetration of the cardiac wall was established by the appearance of fresh arterial blood in the LuerLok fitting of the hypodermic needle. In addition, blue-fluorescent polystyrene beads (10 μm diameter; Invitrogen, Molecular Probes) were coinjected with cancer cells and their detection in the adrenal glands was utilized to confirm successful inoculation in the blood circulation (51,52). Animals were sacrificed after 72 hours, and adrenal glands and bones were fixed in 4% formalin for 48 hours.…”
Section: Figure 10mentioning
confidence: 99%
“…Sections of each hind leg and soft-tissue organs were transferred on glass slides, stored at -20°C, and examined for cancer cells using a Zeiss AX10 fluorescence microscope connected to a Nuance multispectral imaging system (CRI) with a measurement module included in the analysis software (v. 2.4). Bright field and fluorescence images were acquired with an Olympus DT70 CCD color camera (51,52).…”
Section: Figure 10mentioning
confidence: 99%
“…Cells were cultured at 37°C and 5% CO 2 in DMEM supplemented with 10% fetal bovine serum (Hyclone) and 0.1% gentamicin (Invitrogen). The PC3-ML cells were engineered to stably express enhanced variant of green fluorescent protein (GFP) by using a lentiviral vector from America Pharma Source (17).…”
Section: Cell Lines and Cell Culturementioning
confidence: 99%
“…This scenario is likely determined by the fact that disseminated cancer cells may benefit from additional trophic support that does not derive from bone matrix degradation but is readily available in the bone marrow environment and, therefore, not necessarily dependent on osteoclast activity. Indeed, our previous studies have shown that isolated cancer cells and small foci detected shortly after their initial colonization of the bone are either independent of or much less reliant on spatial interactions with osteoclasts than are larger, more advanced lesions (17). Thus, it seems plausible that other compounds used in combination with bisphosphonates, such as those that target survival and/or proliferative pathways in cancer cells, may result in pronounced curative effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation